Study of heavy metal in two species of marine fishes in the coastal waters of Lattakia City - محمد, يمام; حازم كراوي; حسام الدين لايقه (Latakia University Journal -Basic Sciences Series, 2023)
This research focused on determining the concentrations of lead (pb) and cadmium (cd) in two types of marine fish (mullet and exotic fish) and in the coastal waters of Lattakia city at the locations of almadinat alriyadia and alkurnish aljanubiuthe southern Corniche, in addition to taking measurements of the hydrochemical factors of marine water (temperature, salinity, pH). Where the concentrations of the studied elements were determined using the atomic absorption spectrometer (Varian 220. Absorption) using flame and graphite techniques. The results showed that there are temporal and spatial changes in the concentrations of the elements, as the highest value of the lead concentration (2.169mg/kg) was recorded in mullet fish at almadinat alriyadia Beach in the summer of 2021, and the lowest value was (1.398mg/kg) in the same location and type of fish in the winter of 2021. The highest value of cadmium concentration (0.197mg/kg) was recorded in mullet fish at almadinat alriyadia Beach in the summer, and the lowest value (0.113mg/kg) in Ghriba fish in alkurnish aljanubiu beach in the winter. The results showed an increase in the concentrations of lead and cadmium in the marine water in the studied locations in summer compared to winter, accompanied by changes in the hydrochemical factors of the studied marine water (temperature, salinity, pH). Key words: heavy metals, coastal waters (Lattakia), lead, cadmium, mullet, ghariba fish.